Pelaksanaan Peraturan Bupati Tulang Bawang Barat Nomor 24 Tahun 2016 tentang Program Bantuan Pendidikan - Agustam Maroba; Zaenal Arifin (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2025)
The current state of education in Tulang Bawang Barat Regency is certainly far from ideal, with many high school graduates unable to continue their education. The primary reason is cost. According to data from the Central Statistics Agency (BPS), in the 2014/2015 publication year, there were 4,032 high school/vocational high school/Islamic high school (SMA/SMK/MA) students in Tulang Bawang Barat Regency, but only 3.56% of them continued on to state universities. Therefore, Tulang Bawang Barat Regent Regulation No. 24 of 2016 concerning the Education Assistance Program was enacted to facilitate students' continued education at state universities. The research question is how Tulang Bawang Barat Regent Regulation No. 24 of 2016 concerning the Education Assistance Program is being implemented and the factors hindering its implementation. Tulang Bawang Barat Regent Regulation No. 24 of 2016 concerning the Education Assistance Program has been successfully implemented. Although several student respondents in the study acknowledged that several inhibiting factors remain, these are due to the widespread delays in providing educational assistance across regional government agencies, particularly delays in disbursing funds, particularly housing funds. The Tulang Bawang Barat Regency Government must prioritize funds related to the implementation of the Educational Assistance Program, which aims to ensure its smooth implementation.